KAJIAN DOSIS PUPUK GUANO DAN PUPUK NPK TERHADAP PERTUMBUHAN DAN HASIL TERONG UNGU (Solanum melongena L.): DOSIS PUPUK GUANO DAN PUPUK NPK TERHADAP PERTUMBUHAN DAN HASIL TERONG UNGU (Solanum melongena L.) - Riris Puspita; Sartono Joko Santosa; Siswadi Siswadi (Innofarm:Jurnal Inovasi Pertanian, 2023)
The study of Guano and NPK Fertilizer Doses on the Growth and Yield of Purple Eggplant (Solanum melongena L.), this research was conducted at the UNISRI Faculty of Agriculture Research Garden located on Jl. Jaya Wijaya, Mojosongo, Banjarsari, Surakarta from November 2022-January 2023 used alluvial soil types. This study aims to study the application of guano and NPK fertilizers on the growth and yield of purple eggplant (Solanum melongena L.). The method used by researcher is a completely Randomized Block Design (RAKL) with 2 treatment factors which were repeated 3 times so that there were 9 treatment combinations. The first factor is the dose of guano fertilizer (G),consisting 3 levels namely: G0 (control), G1 (40 g/plant) and G2 (80 g/plant). NPK fertilizer (N) as the second factor consisting 3 levels namely: N0 (control), N1 (5.5 g/plant) and N2 (11 g/plant). Analysis of variance was used to analyze the observed data and then carried out a further test of BNT at the 5 % level. Parameters in this study include; plant height, leaves number, flowers number, fruit/plants number, fruit length, fruit diameter, and fruit weight. The result showed that guano fertilizer had no effect on the growth and yield of purple eggplant, while NPK fertilizer had effect on the growth and yield of purple eggplant. The best dose of NPK 5,5 g/plant (N1) has an effect on plant height, leaves number, flowers number, fruits/plants number, fruit length, fruit diameter, and fruit weight. There was interaction between guano fertilizer and NPK fertilizer on growth and yield of purple eggplant (Solanum melongena L.).